New Ways for Doing Extensive Reading: Hyperlearning and Cultural Context - Dewi Listia Apriliyanti; Ahmad Munir (Tell : Teaching of English Language and Literature Journal, 2024)
Extensive reading is an effective approach to learning reading. However, this approach is sometimes criticized since it is difficult to measure the improvements in learners’ reading skills. This is due to the primary objective of extensive reading being "reading for pleasure." A refreshment is needed regarding the learning process by adding some supplements to the learning activities. This paper proposes a fresh perspective on implementing an extensive reading project by incorporating the concepts of hyperlearning and cultural context-based reading. Hyperlearning is leveraging technology to improve the reading experience while also solidifying a profound value whilst the cultural context involves selecting texts that are relevant to the interests or background of the learner. By incorporating this approach into their learning experience, learners can improve their language skills while enjoying a more dynamic and personalized learning experience. In this way, learners will cultivate learning habits that are called "hyperlearners".